Automatic generation of objective footprint outlines - Lallensack, Jens N. (PeerJ, 2019)
The objective definition of footprint margins poses a central problem in ichnology. The transition from the footprint to the surrounding sediment is often continuous, and the footprint wall complex, requiring interpolation, approximation, and a priori assumptions about trackmaker anatomy to arrive at feasible interpretations of footprint shapes. The degree of subjectivity of such interpretations is substantial, and outlines produced by separate researchers can differ greatly. As a consequence, statistical shape analysis, regardless if based on linear and angular measurements or on the shape as a whole, are neither fully repeatable nor objective. Here I present an algorithm implemented in the programming environment R that is able to generate continuous footprint outlines based on three-dimensional models—fully automatically, objectively, and repeatable. The approach, which is based on contour lines extracted from the model, traces the outline at the point where the slope of the track wall is steepest. An option for automatic landmark placement is implemented for tridactyl footprints. A case study was carried out on 13 footprints of a single trackway of a theropod trackmaker from the Lower Cretaceous of Münchehagen, Germany. Analysis of the landmark coordinates returned by the script did reproduce statistical results published in an earlier study that was based on human-made interpretative drawings, demonstrating the applicability of the present method for the objective and quantitative shape analysis of tracks. Although faint anatomical details are not always recorded and features not related to the foot anatomy may be included, the generated outlines tend to correspond with human-made interpretative drawings regarding the overall shape. While not suited as a full replacement of interpretative drawings, these generated outlines may be used as an objective basis for such interpretations.